Coherent atomic orbital polarization probes the geometric phase in photodissociation of polyatomic molecules. Issue 3 (8th June 2022) - Weeraratna, Chaya; Suits, Arthur G.; Vasyutinskii, Oleg S.
Abstract: Quantum interference between multiple pathways in molecular photodissociation often results in angular momentum polarization of atomic products and this can give deep insight into fundamental physical processes. For dissociation of diatomic molecules, the resulting orbital polarization is fully understood and consistent with quantum mechanical theory. For polyatomic molecules, however, coherent photofragment orbital polarization is frequently observed but so far has eluded theoretical explanation, and physical insight is lacking. Here, we present a model of these effects for ozone photodissociation that reveals the importance of a novel manifestation of the geometric phase. We show this geometric phase effect permits the existence of coherent polarization in cases where it would otherwise vanish, and cancels it in some cases where it might otherwise exist. The model accounts for measurements in ozone that have hitherto defied explanation, and represents a step toward a deeper understanding of coherent electronic excitation in polyatomic molecules and a new role of the geometric phase. Key Points: Coherent photofragment atomic orbital polarization reveals matter wave interference in dissociation along multiple paths. In diatomic molecules, this is well‐understood, but in polyatomic molecules, large effects are seen but these have defied a rigorous explanation. A model is developed describing these phenomena in the UV dissociation of ozone that accounts for a number of conflicting observations and reveals a new manifestation of the geometric phase in molecular physics. Abstract :